Sediment thickness variations of the Tangshan fault zone in North China from a dense seismic array and microtremor survey. (November 2019) - Bao, Feng; Li, Zhiwei; Tian, Baofeng; Wang, Liaoliang; Tu, Guanghong
Graphical abstract: Highlights: Sediment thickness varies from less than 200 m in the north to ~800 m in the south. Sediment thickness clearly reflects the reactivation of basement faults. Abstract: Reliable knowledge of sediment thickness is beneficial for investigating buried active faults and improving seismic hazard assessments, especially in regions with recent strong earthquakes. In this study, we investigate the basement of sediments around the 1976 Ms 7.8 Tangshan earthquake region, North China using the microtremor horizontal-to-vertical spectral ratio (H/V) method. For the ambient vibration survey, we deploy a dense seismic array (comprising 152 seismographs with inter-station distances of approximately 1–4 km) and obtain the resonance frequency from each seismograph, which indicates the sediment thickness. The H/V method provides a potential tool for inferring the shallow subsurface structure. Based on the relations between resonance frequency and sediment thickness from permanent borehole seismic stations' records, we recover the sediment thickness around the Tangshan fault zone, which varies from less than 200 m in the northern region to more than 800 m in the southern region. Our results are generally consistent with those of previous drilling and geological studies. Variations in the thickness of sediments indicate that the buried fault system has experienced significant modifications over time, which is partially due to predominant tectonic control by the NE-SW trending Tangshan Fault. The obtained thickness of sediments provide an important basis for earthquake strong motion simulations, sediment crustal corrections for travel time tomography and active fault investigations in the Tangshan fault zone.